2013
DOI: 10.1186/1471-2334-13-450
|View full text |Cite
|
Sign up to set email alerts
|

A prospective case–control and molecular epidemiological study of human cases of Shiga toxin-producing Escherichia coli in New Zealand

Abstract: BackgroundShiga toxin-producing Escherichia coli (STEC) O157:H7 and related non-O157 STEC strains are enteric pathogens of public health concern worldwide, causing life-threatening diseases. Cattle are considered the principal hosts and have been shown to be a source of infection for both foodborne and environmental outbreaks in humans. The aims of this study were to investigate risk factors associated with sporadic STEC infections in humans in New Zealand and to provide epidemiological information about the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
45
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(54 citation statements)
references
References 56 publications
4
45
0
Order By: Relevance
“…The evidence of localized transmission of STEC between cattle and humans in New Zealand has advanced our understanding of the epidemiology of sporadic STEC infections in the country and is consistent with environmental- or animal-associated sources of infection rather than more disseminated foodborne outbreaks ( 20 ). Measures to prevent direct contact with animal fecal material in the environment include the wearing of protective clothing, increased hand washing, and targeted education of the population at risk regarding possible sources of STEC infection.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…The evidence of localized transmission of STEC between cattle and humans in New Zealand has advanced our understanding of the epidemiology of sporadic STEC infections in the country and is consistent with environmental- or animal-associated sources of infection rather than more disseminated foodborne outbreaks ( 20 ). Measures to prevent direct contact with animal fecal material in the environment include the wearing of protective clothing, increased hand washing, and targeted education of the population at risk regarding possible sources of STEC infection.…”
Section: Discussionmentioning
confidence: 71%
“…Bovine meat isolates were retrieved from carcass swab samples and bulk meat samples collected at beef-processing plants, so it could be hypothesized that fresh beef meat might be an exposure pathway for humans. However, although various food sources (including beef) were considered as potential risk factors during a nationwide prospective case-control study on sporadic STEC infections in humans, food was not identified as a major exposure pathway of infections in New Zealand ( 20 ). …”
Section: Discussionmentioning
confidence: 99%
“…3,11 In the 5 month study period, detection of VTEC increased by 325% compared with the previous 12 months of data for our region; the median age of patients was higher than that previously reported in NZ (16 years versus <5 years), and the proportion of non-O157 serotypes increased from <20% to 86%. 13,14 In common with other diagnostic laboratories in NZ, prior to the introduction of GP2, VTEC detection in our laboratory was limited to E. coli O157 and testing was performed on pre-selected groups of patients <6 years old and/or with possible haemolytic uraemic syndrome (HUS) noted on the request form. Only where request forms indicated HUS, but E. coli O157 was not isolated, were samples referred to the reference laboratory for stx gene testing.…”
Section: Discussionmentioning
confidence: 99%
“…Transmission of E. coli O157:H7 to humans is principally via contamination of food by animal feces (Jaros et al, 2013). Food products of animal origin have been confirmed as vehicles of disease transmission in case-control studies of VTEC outbreaks and sporadic VTEC infections; these included raw milk (Guh et al, 2010) and undercooked meat products (Chapman et al, 2001).…”
Section: Ajavsmentioning
confidence: 99%